BCG revaccination does not protect against leprosy in the Brazilian Amazon: a cluster randomised trial. - Sérgio S Cunha; Neal Alexander; Mauricio L Barreto; Emilia S Pereira; Inês Dourado; Maria de Fátima Maroja; Yury Ichihara; Silvana Brito; Susan Pereira; Laura C Rodrigues (Public Library of Science (PLoS), 2008)
Although BCG has been found to impart protection against leprosy in many populations, the utility of repeat or booster BCG vaccinations is still unclear. When a policy of giving a second BCG dose to school children in Brazil was introduced, a trial was conducted to assess its impact against tuberculosis, and a leprosy component was then undertaken in parallel.to estimate the protection against leprosy imparted by a second dose of BCG given to schoolchildren.This is a cluster randomised community trial, with 6 years and 8 months of follow-up.City of Manaus, Amazon region, a leprosy-endemic area in Brazil.99,770 school children with neonatal BCG (aged 7-14 years at baseline), of whom 42,662 were in the intervention arm (revaccination).BCG given by intradermal injection.Leprosy (all clinical forms).The incidence rate ratio of leprosy in the intervention over the control arm within the follow-up, in schoolchildren with neonatal BCG, controlled for potential confounders and adjusted for clustering, was 0.99 (95% confidence interval: 0.68 to 1.45).There was no evidence of protection conferred by the second dose of BCG vaccination in school children against leprosy during the trial follow-up. These results point to a need to consider the effectiveness of the current policy of BCG vaccination of contacts of leprosy cases in Brazilian Amazon region.